A Randomized Controlled Trial of Mindfulness-Based Cognitive Therapy for College Students With ADHD. Issue 4 (February 2018) - Gu, Yingqi; Xu, Guangxing; Zhu, Yi
Objective: Between 2% and 8% of college students meet criteria for ADHD, with increased incidence in recent decades. There are very few clinical trials conducted on the meaningful intervention of ADHD in college. Mindfulness-based cognitive therapy (MBCT) effectively treats college students with ADHD and could be more feasibly applied in college mental health clinics.Method: Fifty-four undergraduates with ADHD between ages 19 and 24 were randomized to receive either MBCT or wait-list (WL) during a 6-week intervention phase. ADHD symptoms, neuropsychological performance, and related outcomes were assessed at pre-treatment, post-treatment, and 3-month follow-up.Results: Participants receiving MBCT group showed greater treatment response rates (57%-71% vs. 23%-31%) and experience less anxiety and depression, and greater levels of mindfulness; MBCT participants show greater improvement on neuropsychological performance.Conclusion: MBCT may be a useful intervention for college students with ADHD, improving participants' ADHD symptoms, mindfulness, and sustained attention.